Weighted Lp-Inequalities for the Dunkl Transform - Chokri Abdelkefi; Faten Rached (Journal of Mathematics)
We give, for 1<p≤2, weighted Lp-inequalities for the Dunkl transform, using, respectively, the modulus of continuity of radial functions and the Dunkl convolution in the general case. As application, we obtain, in particular, the integrability of this transform on Besov-Lipschitz spaces.